Optoelectronic Oscillator Based Sensor Using an On-Chip Sensing Probe - Suen Xin Chew; Xiaoke Yi; Wenjian Yang; Chujun Wu; Liwei Li; Linh Nguyen; Robert Minasian (IEEE Photonics Journal, 2017)
An integrated photonic sensor based on an optoelectronic oscillator with an on-chip sensing probe that is capable of realizing highly sensitive and high-resolution optical sensing is presented. The key component is an integrated silicon-on-insulator based microring resonator which is used to implement a microwave photonic bandpass filter (MPBF) to effectively suppress the side modes of the optoelectronic oscillator (OEO) by more than 30 dB, thus generating a peak RF signal that maps the detected optical change into a resulting shift in the oscillating frequency. As an application example, the proposed optical sensor system is employed to detect small changes in temperature, and experimental results demonstrate a highly sensitive optical temperature sensor with an achieved sensitivity of 7.7 GHz/°C. Moreover, the proposed sensing system revealed a 0.02 °C measurement resolution, which is a tenfold improvement to the modest resolution of 0.23 °C of the conventional MPBF system without the OEO loop, rendering it highly suitable for diverse high-resolution sensing applications.